Observation of persistent species temperature separation in inertial confinement fusion mixtures - Brian M. Haines (Nature Portfolio, 2020)
The influence of contaminants is one of the factors hindering self-sustained thermonuclear burn in inertial confinement fusion. Here, the authors present evidence, through simulations and experiments, that contaminants do not fully reach thermal equilibrium, and thus their amount is usually underestimated.